Muscle recruitment pattern of the hamstring muscles in hip extension and knee flexion exercises - Yanagisawa, O.; Fukutani, A. (Journal of Human Kinetics, 2020)
We aimed to compare dynamic exercise performance between hip extension exercises with different knee angles and between knee flexion exercises with different hip angles, and to investigate the recruitment pattern of the hamstrings in each exercise. Seven men performed 4 isokinetic exercises (3 maximal concentric contractions at 30°/s (peak torque) and 30 maximal concentric contractions at 180°/s (total work)): hip extension with the knee fully extended (HEke) and with the knee flexed at 90° (HEkf) and knee flexion with the hip fully extended (KFhe) and with the hip flexed at 90° (KFhf). The recruitment pattern of the hamstrings was evaluated in each exercise using magnetic resonance imaging (T2 calculation). The HEke condition showed significantly greater peak torque than the HEkf condition (p < 0.05). The KFhf condition had significantly greater peak torque and total work values than the KFhe condition (p < 0.05). Although the biceps femoris long head, semitendinosus, and semimembranosus had significantly increased post-exercise T2 values in the HEke (p < 0.05), KFhe, and KFhf conditions (p < 0.01), the T2 increase valueswere significantly greater under the KFhf than the HEke condition (p < 0.05). The semitendinosus showed a significantly greater T2 increase value than other muscles under both KFhe and KFhf conditions (p < 0.05). Performance of hip extension and knee flexion exercises increases when the hamstring muscles are in a lengthened condition. The hamstring muscles (particularly the semitendinosus) are more involved in knee flexion than in hip extension.